The Sound of Programming. - Cerf, Vinton G. (Communications of the ACM, 2018)
A personal narrative is presented that discusses the author's experience of a presentation from entrepreneur Emmanuel Schanzer of the firm Bootstrap World, which offers training for computer programming.